A Long-Acting Curcumin Nanoparticle/In Situ Hydrogel Composite for the Treatment of Uveal Melanoma - Lingxiao Xie; Weizhou Yue; Khaled Ibrahim; Jie Shen (MDPI AG, 2021)
Uveal melanoma (UM) is the most common primary intraocular tumor in adults with high mortality. In order to improve prognosis and survival of UM patients, it is critical to inhibit tumor progression and metastasis as early as possible after the initial presentation/diagnosis of the disease. Sustained local delivery of antitumor therapeutics in the posterior region can potentially achieve long-term UM inhibition, improve target therapeutic delivery to the posterior segments, as well as reduce injection frequency and hence improved patient compliance. To address the highly unmet medical need in UM therapy, a bioinspired in situ gelling hydrogel system composed of naturally occurring biopolymers collagen and hyaluronic acid was developed in the present research. Curcumin with anti-cancer progression, anti-metastasis effects, and good ocular safety was chosen as the model therapeutic. The developed in situ gelling delivery system gelled at 37 °C within two minutes and demonstrated excellent biocompatibility and slow degradation. The curcumin-loaded nanoparticle/hydrogel composite was able to sustain release payload for up to four weeks. The optimized nanoparticle/hydrogel composite showed effective inhibition of human UM cell proliferation. This novel nanoparticle/in situ hydrogel composite demonstrated a great potential for the treatment of the rare and devastating intraocular cancer.